Monitoring schedule time using exponentially modified Gaussian distribution. Issue 4 (3rd July 2020) - Ara, Jehan; Ali, Sajid; Shah, Ismail
ABSTRACT: Control charts are efficient process monitoring tools used to distinguish between assignable and natural variations. This article presents a new time-between-events chart to monitor the scheduled time. In particular, exponentially modified Gaussian distribution is considered in the construction of the control chart. The performance of the chart is evaluated in terms of average run length and coefficient of variation of the run length. To show the significance of the proposed chart, the data on time in hours between the detection of cancer cells using 3 um erlotinib and schedule time in minutes of an employ are considered.